The impact of antifungals on toll-like receptors - Mihu, Mircea R.; Pattabhi, Rodney; Nosanchuk, Joshua D. (Frontiers in Microbiology, 2014)
Fungi are increasingly recognized as major pathogens in immunocompromised individuals. The most common invasive fungal infections are caused by Candida spp., Aspergillus spp. and Cryptococcus spp. Amphotericin B has remained the cornerstone of therapy against many fulminant fungal infections but its use is limited by its multitude of side effects. Echinocandins are a newer class of antifungal drugs with activity against Candida spp. and Aspergillus spp. and constitutes an alternative to amphotericin B due to superior patient tolerability and fewer side effects. Due to their excellent bioavailability and oral availability, azoles continue to be heavily used for simple, such as fluconazole for candidal vaginitis, and complex diseases, such as voriconazole for aspergilloisis. The objective of this paper is to present current knowledge regarding the multiple interactions between the broad spectrum antifungals and the innate immune response, primarily focusing on the toll-like receptors.